Recent Advances in Biofluid Mechanics and Bio- and Hemorheology Collating Recent Advances in Predicting Complex Behavior of Human Blood With Thixo-Elasto-Visco-Plastic Models and Sequence of Physical Process - Armstrong, Matthew; Pincot, Andre; Rogers, Simon; Knight, Thomas; Bailey, Dorian (Frontiers in Physics, 2022)
For years industrial polymer production has driven the development of rheological models to characterize the flow of materials. With the evolution of these models has come a corresponding advancement in the understanding of the complex mechanical properties. Recent efforts have been focused on modeling the behavior of complex fluids such as blood, whose microstructure leads to has simultaneous characteristics such as: thixotropy; elasticity; plasticity; and an evolving viscosity (part of which originates with the rouleaux’s evolution). The specific complex behavior of human blood can be analyzed via the analysis of Large-Amplitude-Oscillatory-Shear (LAOS) and Small-Amplitude-Oscillatory-Shear (SAOS) response tests. Unique features of human blood cannot be replicated in legacy steady-state models and, thus, have required the development of more comprehensive models capable of accurately fitting both steady state, transient flow and oscillatory shear flow. Expanding upon prior transient models, collaboration between the Chemical Engineering departments of the United States Military Academy and the University of Delaware has produced a new model, tensorial enhanced structural stress thixotropic-viscoelastic model (t-ESSTV). This model can capture the timescales contained within the plasma and individual red blood cells viscoelasticity and the thixotropic timescales associated with rouleaux breakdown and aggregation. The efficacy of t-ESSTV is demonstrated with a single Donor before consolidating the best fit model parameters of twelve Donor sets of rheological data. We then show the parametric correlations between model and physiological parameters and with the models’ prediction of microstructure, we correlate microstructure with the ‘elastic, solid-like’ metrics as computed by Sequence of Physical Processes (SPP).